High sugar diet-induced fatty acid oxidation potentiates cytokine-dependent cardiac ECM remodeling. - Gera, J.; Kumar, D.; Chauhan, G.; Choudhary, A.; Rani, L.; Mandal, L.; Mandal, S. (Journal of Cell Biology, 2024)
Context-dependent physiological remodeling of the extracellular matrix (ECM) is essential for development and organ homeostasis. On the other hand, consumption of high-caloric diet leverages ECM remodeling to create pathological conditions that impede the functionality of different organs, including the heart. However, the mechanistic basis of high caloric diet-induced ECM remodeling has yet to be elucidated. Employing in vivo molecular genetic analyses in Drosophila, we demonstrate that high dietary sugar triggers ROS-independent activation of JNK signaling to promote fatty acid oxidation (FAO) in the pericardial cells (nephrocytes). An elevated level of FAO, in turn, induces histone acetylation-dependent transcriptional upregulation of the cytokine Unpaired 3 (Upd3). Release of pericardial Upd3 augments fat body-specific expression of the cardiac ECM protein Pericardin, leading to progressive cardiac fibrosis. Importantly, this pathway is quite distinct from the ROS-Ask1-JNK/p38 axis that regulates Upd3 expression under normal physiological conditions. Our results unravel an unknown physiological role of FAO in cytokine-dependent ECM remodeling, bearing implications in diabetic fibrosis.